Analisis Hasil Belajar Siswa pada Materi Pokok Hidrokarbon Berdasarkan Gaya Belajar (Studi Pada Siswa Kelas X SMA Negeri 1 Bontolempangan Kabupaten Gowa) - Fahruddin Ilham Nur; Muhammad Danial; Diana Eka Pratiwi (Jurusan Kimia FMIPA UNM, 2022)
Analysis of Student Results with subject matter is Hydrocarbon Based Learning Styles (Studies in Class X SMAN 1 Bontolempangan Gowa). Chemistry Education Program. Department of Chemistry. Faculty of Mathematics and Sciences. Makassar State University (led by Muhammad Danial and Diana Eka). This study was a descriptive study aimed to describe the results of student learning in SMA Negeri 1 Bontolempangan Gowa district based on learning style in the subject matter of hydrocarbons. Subjects are consist of 60 students. This study method using a questionnaire style of learning as much as 12 statements and test results to learn as much as 20 grains of questions to each sample by taking a score dominant learning style statement and an average score of each class learning outcomes. The results show that the class X.1 learning styles, there are 6 groups consisting of auditory, visual, kinesthetic, auditory-visual, kinesthetic and visual-auditory-visual-kinesthetic with each gain medium category of learning outcomes. This indicates that the dominant group of students with three styles. X.2 there are 4 visual and auditory learning style categories were, kinesthetic and A-V-K with the high category. While in class learning styles X.3 are auditory, kinesthetic with high category and auditory-visual learning style with the medium category.